Economic Implications of Sustainable Hospitality Industry: A Systematic Review - Pandu Adi Cakranegara; Windy Eka Saputri (STIE Pariwisata API Yogyakarta, 2025)
This study reviews how sustainable practices affect financial performance in the hospitality industry. Growing environmental awareness, government rules, and changing customer expectations are pushing hotels, resorts, and restaurants to include sustainability in their daily operations. Using the SALSA (Search, Appraisal, Synthesis, and Analysis) method, 32 relevant studies were reviewed from major academic databases. The results show that sustainability can improve profits when treated as a long-term investment rather than a short-term cost. Key actions such as saving energy, reducing waste, using renewable energy, and applying circular economy ideas help lower costs and attract customers who care about the environment. Green certifications and open communication about eco-friendly efforts also strengthen brand image, build customer trust, and increase occupancy rates. Government incentives and clear regulations further support green innovation and reduce financial challenges. However, businesses still face barriers such as high initial costs, limited funding access, and inconsistent ways of measuring economic results. Overall, this review finds that sustainability and financial success can go hand in hand. Sustainable business models can help hospitality businesses stay competitive, resilient, and profitable in the long run. Future research should focus on finding the most cost-effective green practices and exploring regional differences in sustainable performance.